2010
DOI: 10.1590/s0004-27302010000800011
|View full text |Cite
|
Sign up to set email alerts
|

A novel GNAS mutation in an infant boy with pseudohypoparathyroidism type Ia and normal serum calcium and phosphate levels

Abstract: The objective of this study was to describe a new mutation in GNAS in a family with pseudohypoparathyroidism type Ia (PHP Ia), a rare osteometabolic disease. An 8-month-old boy was seen by an Endocrinologist due to obesity and low growth velocity. Noteworthy, his mother exhibited typical Albright hereditary osteodystrophy (AHO) phenotype. The clinical diagnosis of PHP Ia was suspected. The GNAS coding region from mother and son was amplified and directly sequenced. A novel heterozygous missense mutation (c.673… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…There is some evidence to suggest that the Gs alpha mutation is paternally transmitted in patients with PPHP and maternally transmitted in patients with PHP-Ia. The gene may be imprinted in a tissue-specific manner6,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence to suggest that the Gs alpha mutation is paternally transmitted in patients with PPHP and maternally transmitted in patients with PHP-Ia. The gene may be imprinted in a tissue-specific manner6,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…The patient had normal serum concentrations of calcium and phosphate for his age, and just his elevated levels of TSH and his mother’s background was compatible with the diagnosis of PHP-Ia [17]. Mariana Tenorio Antunes Reis et al [20] have also reported an infant boy with AHO phenotype, normal calcium and phosphate levels, whose mother was diagnosed as PHP-Ia. The functional analysis of GNAS exons showed a novel heterozygous missense mutation in exon 5 of GNAS.…”
Section: Discussionmentioning
confidence: 99%
“…The GNAS gene is located on the long arm of chromosome 20 in the region 13.1 -13.2 and contains 13 exons. The inactivating mutations have been detected in all exons, with 20 % of the mutations occurring in exon 7 (2,3) .…”
Section: Introductionmentioning
confidence: 99%